2009
DOI: 10.1007/s12098-009-0044-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis in Indian children with achondroplasia — utility of molecular diagnosis

Abstract: Further study of these two cases is needed in order to define other genotypes resulting in achondroplasia. Postnatal diagnosis of achondroplasia depends on clinical and radiological features. Mutation detection is mainly useful for prenatal diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The estimated reported prevalence is approximately 1 in 15,000 people in the Indian population. 4 Although accurate prevalence estimation in a rare disease is challenging, reported estimates of achondroplasia birth prevalence vary widely, ranging from 1 in 10,000 to 40,000 newborns worldwide based on a few selected references. 5 This is a nonlethal skeletal dysplasia with a normal or near normal life expectancy beyond infancy.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated reported prevalence is approximately 1 in 15,000 people in the Indian population. 4 Although accurate prevalence estimation in a rare disease is challenging, reported estimates of achondroplasia birth prevalence vary widely, ranging from 1 in 10,000 to 40,000 newborns worldwide based on a few selected references. 5 This is a nonlethal skeletal dysplasia with a normal or near normal life expectancy beyond infancy.…”
Section: Introductionmentioning
confidence: 99%
“…This group had suggested that all the patients with ACH were to be initially screened for the presence of two common mutations in FGFR3 gene, c.1138G>A and c.1138G>C. This was in turn proved in 81% of the sporadic ACH cases from Lucknow, India. [ 39 ] The report on molecular analysis of 60 Indian patients affected with mucopolysaccharidosis type I (MPS I; n = 30) and mucopolysaccharidosis type II (MPS II; n = 30) disorders was considerable for the presence of recurrent pathogenic variants in both the disorders. [ 40 ] Mutations in affected families of Morquio A syndrome (MPS IV A, n = 68 families, GALNS ) and GM1 gangliosidosis ( n = 50 families, GLB1 ) disorders were reported by Bidchol et al .…”
Section: Resultsmentioning
confidence: 99%
“…Komplikasyonlara yönelik beyin cerrahisi ve ortopedi ameliyatları gerekebilir. 35,36 Akondroplazide rol oynayan moleküler süreçlerin daha iyi anlaşılmasıyla, FGFR3 ligandlarını, FGFR3 sinyal yolağını bloke etmeye çalışan tirozin kinaz inhibitörleri ve C-tipi natriüretik peptit analogları (vosoritid) gibi çeşitli ilaç çalışmaları devam etmektedir.…”
Section: Akondroplaziunclassified